1987
DOI: 10.1161/01.str.18.2.426
|View full text |Cite
|
Sign up to set email alerts
|

Breathing 100% oxygen after global brain ischemia in Mongolian Gerbils results in increased lipid peroxidation and increased mortality.

Abstract: Exposure of Mongolian gerbils to a 100% oxygen atmosphere after 15 minutes of global brain ischemia resulted in a marked increase in the production of pentane, an in vivo product of lipid peroxidation. Much less pentane production occurred in animals subjected to global brain ischemia then exposed to an air atmosphere and in animals exposed to a 100% oxygen atmosphere without ischemia. Gerbils placed in 100% oxygen for 3-6 hours after 15 minutes of ischemia also had a threefold increase in 14-day mortality com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(86 citation statements)
references
References 21 publications
2
83
0
1
Order By: Relevance
“…This practice has been questioned by results obtained with animal models demonstrating improved neurologic outcome using postischemic ventilation with O 2 concentrations as low as 21% [15,16,72]. Our present findings demonstrating reduced hippocampal protein tyrosine nitration and retention of PDHC enzyme activity with normoxic resuscitation support the need for additional preclinical and clinical studies to resolve this issue.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 69%
“…This practice has been questioned by results obtained with animal models demonstrating improved neurologic outcome using postischemic ventilation with O 2 concentrations as low as 21% [15,16,72]. Our present findings demonstrating reduced hippocampal protein tyrosine nitration and retention of PDHC enzyme activity with normoxic resuscitation support the need for additional preclinical and clinical studies to resolve this issue.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 69%
“…Several studies have demonstrated that when animals are hyperoxic during reperfusion following global cerebral ischemia, brain tissue oxidative stress markers, impaired cerebral energy metabolism, neuronal death, and neurologic impairment are greater than what is observed following normoxic reperfusion (Balan et al, 2006;Liu et al, 1998;Mickel et al, 1987;Richards et al, 2006;Vereczki et al, 2006). These findings have led to the concept that brain tissue oxygenation in excess of what is necessary to saturate metabolic O 2 utilization is toxic during early reperfusion, when altered intracellular conditions, e.g., pH, [Ca 2+ ], etc., may either promote the formation of reactive oxygen species (ROS) or inhibit their detoxification (Rosenthal and Fiskum, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…18) Also, breathing 100% oxygen after 15 minutes of global brain ischemia not followed by reperfusion increased lipid peroxidation and mortality in gerbils. 11) On the other hand, HBO did not increase brain lipid peroxidation if administered to rats after 10 minutes of focal brain ischemia not followed by reperfusion, 24) and HBO increased free radicals but not lipid peroxidation if started within 1 minute of reperfusion following cerebral ischemia in a rabbit model. 12) Therefore, we suspect that HBO probably increases free radicals and lipid peroxidation, particularly in patients with embolic stroke in whom recanalization commonly occurs at various times.…”
Section: Discussionmentioning
confidence: 92%
“…With the exception of three studies, 3,15,20) the major criticism of most clinical investigations has been the lack of controlled prospective analysis. 14) Oxygen free radicals, which may be produced by HBO therapy 6) or by breathing 100% oxygen, 11) are likely to be important in the mechanism of damage caused by cerebral ischemia. 22) Edaravone, a novel free radical scavenger, is reported to be effective in the treatment of patients with acute ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%